Countercyclical Liquidity Policy and Credit Cycles: Evidence from Macroprudential and Monetary Policy in Brazil - Blanco Barroso, João Barata R; Barbone Gonzalez, Rodrigo; Peydró, José-Luis; Nazar Van Doornik, Bernardus F (The Review of Corporate Finance Studies, 2026)
Abstract We analyze how countercyclical liquidity policy—via reserve requirements (RRs)—affects the credit cycle. For identification, we exploit supervisory credit register data and RR changes in Brazil made for monetary and macroprudential purposes and affecting banks differently. We find that countercyclical liquidity policy smooths credit supply cycles at the loan and firm levels. The effects of easing during crises are three times stronger than are those of tightening during booms, particularly for low-risk firms. We also explore interest rate policy. Credit supply effects are stronger among high-risk firms and during tightening, when interest rates are more effective than RRs.